INDUSTRIAL MINERALS IN WEST KALIMANTAN AND THEIR UTILIZATION FOR CERAMIC PRODUCTS - SUBARI SUBARI; SURIPTO SURIPTO (Indonesian Mining Journal, 2008)
The Province of West Kalimantan has abundant source of industrial minerals such as kaolin, ball clay, quartz and zircon that can be utilized as ceramic raw materials. These materials are spread out in Regencies of Sambas, Singkawang, Bengkayang, Sanggau and Sintang. From various industrial minerals found in West Kalimantan, only clay and kaolin have been utilized by the ceramic industries in West Kalimantan, West Java, Central Java, East Java and Bali. The other industrial minerals such as bauxite, zircon, ilmenite, quartz still have not been utilized for ceramics commodity. Therefore to empower all industrial mineral types from these areas as ceramic raw materials, it is necessary to do a circumstantial and comprehensive study of those minerals based on the result of preliminary research related to ceramic raw materials, whether by using them directly for ceramic products or through processing beforehand. From this study, it is expected that the industrial minerals in West Kalimantan can be empowered to be optimally utilized for white or coloured ceramic bodies, glaze, refractory and other ceramic products.